Work Organization, Job Stress and Work-Related Musculoskeletal Disorders. - Carayon, Pascale; Smith, Michael J.; Haims, Marla C.
Recent studies indicate potential links among work organizations, job stress and work-related musculoskeletal disorders (WRMDs). In this paper we propose several pathways for a theoretical relationship between job stress and WRMDs. These pathways highlight the physiological, psychological and behavioral reactions to stress that can affect WRMDs directly and indirectly. One model stipulates that psychosocial work factors (e.g. work pressure, lack of control), which can cause stress, might also influence or be related to ergonomic factors such as force, repetition, and posture that have been identified as risk factors for WRMDs. In order to fully understand the etiology of WRMDs, it is important to examine both physical ergonomic and psychosocial work factors simultaneously. Smith and Carayon-Smith (1989) have proposed a model of the work system for stress management that provides a useful framework for conceptualizing the work-related factors that contribute to WRMDs. Practical applications of this research include practitioners taking into account psychosocial work factors and job stress in their efforts to reduce and control WRMDs.